Inovasi Media Pembelajaran Matematika Berbasis PMRI Untuk Meningkatkan Literasi Numerasi Siswa SMP - Merli Handayani; Sugeng Sutiarso; Chika Rahayu (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study aims to develop an Android-based interactive learning media using the Indonesian Realistic Mathematics Education (PMRI) approach to facilitate students’ numeracy literacy skills. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 26 seventh-grade students from a junior high school in Pesawaran Regency. The instruments used included expert validation questionnaires, student and teacher response questionnaires, as well as pretest and posttest assessments. The results showed that the developed media met the criteria of validity, practicality, and effectiveness. The material expert validation obtained an average score of 4.20 (valid), while the media expert validation obtained an average score of 4.33 (very valid). The teacher response showed an average score of 4.44 (practical), while the student responses reached an average score of 4.54 (very practical). The effectiveness of the media was indicated by the improvement in students’ numeracy literacy skills, with classical completeness reaching 81%. Therefore, the developed Android-based interactive learning media using the PMRI approach is considered feasible and shows potential effectiveness in facilitating students’ numeracy literacy skills within the research context.Keyword: interactive learning media, Android, PMRI, numeracy literacy